PYROSEQUENCING- PRINCIPLES AND APPLICATIONS: Life Science-Molecular Biology - MD. FAKRUDDIN; CHOWDHURY, ABHIJIT; HOSSAIN, MD. NUR; SHAHNEWAJ BIN MANNAN, KHANJADA; MOHAMMAD MAZUMDAR, REAZ (International Journal of Life Science and Pharma Research, 2012)
Pyrosequencing is the first alternative to the conventional Sanger method for de novo DNA sequencing. Pyrosequencing is a DNA sequencing technology based on the sequencing-by-synthesis principle. It employs a series of four enzymes to accurately detect nucleic acid sequences during the synthesis. Pyrosequencing has the potential advantages of accuracy, flexibility, parallel processing, and can be easily automated. Furthermore, the technique dispenses with the need for labeled primers, labeled nucleotides, and gel-electrophoresis. Pyrosequencing has opened up new possibilities for performing sequence-based DNA analysis. The method has been proven highly suitable for single nucleotide polymorphism analysis and sequencing of short stretches of DNA. Pyrosequencing has been successful for both confirmatory sequencing and de novo sequencing. By increasing the read length to higher scores and by shortening the sequence reaction time per base calling, pyrosequencing may take over many broad areas of DNA sequencing applications as the trend is directed to analysis of fewer amounts of specimens and large-scale settings, with higher throughput and lower cost. This article considers key features regarding different aspects of pyrosequencing technology, including the general principles, enzyme properties, sequencing modes, instrumentation, limitations, potential and future applications.